Who controls the board in non-profit organizations? The case of private higher education institutions in Colombia (2018)
How should the governance system in a non-membership non-profit organization be designed? This organizational form has no shareholders; instead, donors provide funds. Thus, at the organizational level, the board of directors could have all the power. Under this legal form, who controls the board? If too powerful, boards could misuse resources or distract the organization from its foundational goals. We examine the case of private higher education institutions (HEIs) in Colombia and the balance of power in university governance systems which feature this organizational form. Most HEIs in our sample have a kind of assembly of representatives as the governance body with the highest authority and able to appoint and control the board. We specifically discuss the assemblies’ reason for being, structure, and functions in private HEIs in Colombia. We analyze a total of 204 HEI governance structures and find governance arrangements with the characteristics of an assembly of representatives in 154 (75.9%). Our analysis highlights features in some of these governance bodies that could lead to overly powerful assemblies (e.g., founder donors with tenure for life). Clearly, a proper balance of power is required to avoid rent-seeking behaviors or the pursuit of harmful private non-monetary benefits from assembly members as well as boards. © 2017, The Author(s).